Criar o público não-estatal ou tornar público o estatal? Dilemas da educação em meio à crise do Estado - Márcio da Costa (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
The forms of distribution of resources and responsibilities with respect to educational policy are at present diversified. The scope of traditional state action has been the object of forceful appeals and policies of expressive encouragement to community participation, particularly in less economically developed countries. These find expression in programmes aimed at extending access to schooling to populations who until that time have been denied such benefits and emphasise alterations in management style based on community participation. Such programmes change the trajectory of expansion followed by school systems world-wide with regard to the conception of what constitutes essentially state activity. Based on this sociological reflection, the text discusses the arguments that sustain such types of programme which are taken to be more democratic and inclusive.